2008
DOI: 10.1093/ajcn/87.6.1883
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic status and fruit and vegetable intake among whites, blacks, and Mexican Americans in the United States

Abstract: The positive association of neighborhood SES with fruit and vegetable intake is one important pathway through which the social environment of neighborhoods affects population health and nutrition for whites, blacks, and Hispanics in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
269
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(304 citation statements)
references
References 47 publications
(41 reference statements)
20
269
5
2
Order By: Relevance
“…Neighborhood SES shapes the social, service, and physical environments of residents, 16,19,46,47 thereby exposing them to behaviors (e.g., physical activity and diet) [48][49][50][51][52] and essential resources (e.g., education, employment, and community services) [53][54][55] that may be beneficial or detrimental to health. 54 Levels of air pollution also tend to be higher in poor compared to wealthier neighborhoods, 56 and poor neighborhoods lack safe and accessible places to walk and exercise, as well as sources of healthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood SES shapes the social, service, and physical environments of residents, 16,19,46,47 thereby exposing them to behaviors (e.g., physical activity and diet) [48][49][50][51][52] and essential resources (e.g., education, employment, and community services) [53][54][55] that may be beneficial or detrimental to health. 54 Levels of air pollution also tend to be higher in poor compared to wealthier neighborhoods, 56 and poor neighborhoods lack safe and accessible places to walk and exercise, as well as sources of healthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, women, married and white people, those with better education and income, physically active, non-smokers, and with moderate alcohol consumption habits tend to consume adequately FV [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Persons in these groups tend to live in neighborhoods with poor access to supermarkets and greater-than-average access to convenience stores and small grocery stores. [16][17][18][19][20] One study has shown that neighborhood-level measures of socioeconomic status are associated with fruit and vegetable intake independent of individual-level socioeconomic status, suggesting that the foods available in neighborhoods may be contributing to socioeconomic and racial health disparities in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] One study has shown that neighborhood-level measures of socioeconomic status are associated with fruit and vegetable intake independent of individual-level socioeconomic status, suggesting that the foods available in neighborhoods may be contributing to socioeconomic and racial health disparities in the USA. 13 If the "food environment" does have an important influence on purchases and consumption, one possible approach to promoting healthy diets in disadvantaged groups would be to provide incentives to stores that sell a healthier mix of foods to locate in or near the neighborhoods in which they live. For such an approach to be effective, incentives must be tied to criteria that the stores meet for the availability and accessibility of both healthy and unhealthy foods, such as minimum shelf lengths for healthy items and maximum shelf lengths for unhealthy items.…”
Section: Introductionmentioning
confidence: 99%